Analysis of Asbabun Nuzul Education Verses in Surah Luqman - Simbolon, Nur Rafidah Mahdiyyah; Asha, Asha; Sakinah, Fitri; Maulidya, Anisa; Ediz, M. Hidayat; Yanti, Novia (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2023)
Asbabun nuzul is the process of the revelation of the Quran at certain times, the cause of its revelation was based on an event that occurred, or the revelation was caused by questions from the Arabs to the Prophet. This research discusses the benefits asbabun nuzul, the concept of education, as one of the story teaching methods applied by the Prophet. So the method used in this research uses library research methods which include book sources, journals and historical stories. The results of research studies on the relevance of the causes of the revelation and Islamic law can improve student learning outcomes effectively and build moral character and exemplary attitudes among students, accompanied by an analysis of the asbabun nuzul verses on education in Surah Al-Luqman verses 12-19 which contain them. Islamic faith and sharia education.